Isolation and structural determination of pentacyclic triterpenoids from the leaves of Gymnosporia chevalieri tard - Doan, Thi Ai Nghia; Hoang, Thi Nhu Hanh; Le, Tuan Anh; Le, Thi Hong Van; Vo, Quoc Hung; Nguyen, Thi Hoai; Ho, Viet Duc (Tạp chí Y Dược Huế, 2024)
Background: The genus Gymnosporia, belonging to the Celastraceae family, which comprises approximately 116 species globally, with 8 species identified in Vietnam. This work initially describes the extraction, isolation, and structural identification of six triterpenoids from G. chevalieri collected in Vietnam. Materials and methods: The leaves of G. chevalieri were subjected to extraction through immersion, followed by a liquid-liquid partition process using organic solvents. Compounds were isolated using a combination of thin-layer chromatography and column chromatography. Their structures were determined based on 1D-, 2D-NMR as well as by comparison with the reported spectroscopic data. Results & Conclusion: The chemical constituents of G. chevalieri was reported for the first time. Six pentacyclic triterpenoids have been isolated and determined including mixture of α-amyrin (1a) and β-amyrin (1b), β-amyrenonol (2), 3-oxofriedelan-29-ol (3), taraxastane-3β,20R-diol (4), and taraxastane-3β,20S-diol (5).